(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The experiment was carried out during 2020-2021 in a citrus orchard,a 15-year-old mayer lemon in order to study the effect of foliar spraying with different concentrations of the micro-elements and magnesium on some leaf specifications and fruit quality . The experiment included four spraying treatments with water only, with micro-elements and magnesium with concentrations 1ml/l and 1.5ml/l and 2ml/l) respectively. The clorophyllcontent,leafarea,percentage of dry matter of leaves and fruits,physical and chemical properties of fruits were estimated. The result of the study,it was found that the treatment of spraying with micro-elements and magnesium with high concentration T4 (2ml/l) was significantly superior in all the studied indicators on the treatments of the control and the treatment of spraying with low concentrationT2(1 ml/l). The treatment achieved the high concentration 2ml/l in relation to the average length 7.42 cm,diameter 5.7 cm,hardness 0.63 kg/cm2,weight of fruit72.14 g and size 86.42cm3 ,the percentage of juice reached 35.99%, while the thickness of the fruit rind 0.236 cm. The percentage of TSS was11.54% , Amount of vitamin C 46.35 mg/100g fresh material,While highest total chlorophyll content of leaves reached2.46mg/g . the highest leaf area reached 37.76 cm3,while the control treatment achieved the lowest values in all studied indicators.